O papel do poder judiciário num cenário de crise institucional: uma análise à luz da teoria dos sistemas de Niklas Luhmann. - Silva, José Elio Ventura da (2022)
This thesis aims to understand the role of the Judiciary, in particular, the Federal Supreme Court, in a scenario of institutional crisis in the face of the need to observe the separation of powers on the one hand and the prohibition of denial of justice (non liquet) on the other. Law, according to Niklas Luhmann's Systems Theory, has as its founding element the congruent generalization of normative expectations. Politics, in turn, operates on the basis of collectively binding decision-making. In a context of extreme social complexity and great contingency, there is a relationship of reciprocity between the systems, which generates infinite possibilities for action. Although paradoxical, partial systems must function operationally closed, however, cognitively open. It is an absolutely necessary relationship for the establishment of the communications network within society. In this context, the risk is inexorable, characteristic of these relationships. It is up to the law, therefore, to stabilize these expectations. Thus, in spite of the political and legal systems being structurally linked by the Constitution, the distinctions need to be considered, under penalty of denaturing the operations, with the culmination in the corruption of the codes. The judicial decision becomes, therefore, a starting point for structuring the discussion, followed by an analysis of the political and legal systems immersed in the aforementioned crisis. The Judiciary plays an important role in this context of hypercomplexity of relationships, even because it is demanded every day more frequently to express its opinion on issues of a political nature, notably the Federal Supreme Court. In this sense, the thesis, based on bibliographic research, theoretical review and document analysis, deals with a subject of enormous complexity: understanding the role of the Judiciary in this scenario, from the perspective of Niklas Luhmann's Systems Theory. No less complex, certainly, is the chosen theory, however, a critical look at the role of law in this context is necessary. It is believed that, although the selected theory is not immune to criticism, it corresponds to a model that satisfactorily meets the expectations presented here and, without closing its eyes to said criticisms, the theory is able to indicate potential responses to the problem presented, precisely because of it is an evolutionary theory of law and society.